An Empirical Investigation on the Acceptance and Adoption of E-Commerce Among Internet Users in Malaysia - Shaidatul Ak'mar, Yahya (2011)
This study examines the effect of three factors on the acceptance and adoption of electronic commerce among internet user in Malaysia. A review of the literature shows that owner characteristics such as lack of knowledge and perceived lack of trust are significant inhibitors while environment characteristics such as government support are significant motivators of electronic commerce in Malaysia. A questionnaire survey was conducted in 150 respondents of internet user in Kuala Lumpur. A total of 108 valid responses were obtained. Stratified random sampling was adopted over other techniques to enhance representativeness. Data analysis shows that significant relationship exists between each of the three variables and electronic commerce adoption among internet user in Kuala Lumpur. Security issues emerged as the most important factor influence the acceptance and adoption of e-commerce. This factor is followed by government support and knowledge in information technology.